1979
DOI: 10.1159/000207635
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Dysfunction in Patients with Vitamin B<sub>12</sub> Deficiency

Abstract: 10 cases of pernicious anaemia are reported in which 6 had abnormal aggregation with epinephrine, 3 with fibrinogen, 2 with ADP, and 2 with ristocetin. 5 patients had thrombocytopenia and 3 of these had a prolongation of the bleeding time. These abnormalities were normalized after vitamin B12 treatment. After treatment, platelet size changed toward a smaller diameter, but platelet size, however, was not significantly different from the normal platelet size distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In most instances, such reactive thrombocytosis is described as asymptomatic but various thrombo-embolic complications, including deep vein thrombosis, coronary infarction and cerebral venous thrombosis, have been reported. 17,19 During follow-up, one of our patients had sudden-onset altered consciousness with features of raised intracranial pressure. He rapidly deteriorated and died.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In most instances, such reactive thrombocytosis is described as asymptomatic but various thrombo-embolic complications, including deep vein thrombosis, coronary infarction and cerebral venous thrombosis, have been reported. 17,19 During follow-up, one of our patients had sudden-onset altered consciousness with features of raised intracranial pressure. He rapidly deteriorated and died.…”
Section: Discussionmentioning
confidence: 87%
“…Ingeberg & Stoffersen, while reporting platelet dysfunction in Cbl deficiency, also noticed thrombocytosis in three of ten cases. 19 The mechanism by which thrombocytosis develops following thrombocytopenia is thought to be a feedback process controlling thrombopoiesis. 17 During thrombocytopenia, the thrombopoietin levels are increased, which might be responsible for the brisk rise in the platelet count once the deficiency is corrected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to several single case reports [1,2,7,8,10,17,19,20,22,23,29], two larger series have demonstrated the high frequency of moderate thrombocytosis in POEMS syndrome [4,24]. Nevertheless, the unique and paradoxical combination of vitamin B 12 deficiency, which is usually associated with thrombocytopenia [9], and thrombocytosis has been reported only once in POEMS syndrome before [28]. PO-EMS syndrome is characterised by a massive increase in serum VEGF levels, which originates from platelets [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…Both of our patients had pancytopenia with bleeding manifestations. Bleeding manifestations in megaloblastosis have been reported to be up to 25% by various workers [3,4] The commonly described hemorrhages are retinal hemorrhages and purpuric spots. Bleeding in the form of hemtemesis, hemoptysis and even life-threatening bleeding was described by Marwaha et al [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhage can occur even with high platelet counts because of platelet dysfunction associated with megaloblastosis. Abnormal platelet aggregation with epinephrine, adenosine diphosphate (ADP) and ristocetin was demonstrated in six out of 10 patients by Ingeberg and Stoffersen [3]. Ghosh et al [4] also demonstrated impaired aggregation to ADP, collagen epinephrine and ristocetin in four out of 17 patients in their series with megaloblastic anemia.…”
Section: Discussionmentioning
confidence: 99%